A Fast Handoff Scheme for Streaming Service in Wireless Sensor Networks. (22nd March 2015) - Yun, Jeongbae; Khan, Murad; Han, Kijun
Abstract : The IEEE 802.15.4 standard is a rapidly growing technology for short-range communications and low rate Wireless personal area networking. The standard has been widely accepted as the de facto standard for wireless sensor network (WSN) because of its low cost deployment and remarkable applications. The mobility management in the existing WSN has highly suffered from different issues like high packet loss and delay because the current mobility management in IEEE 802.15.4 lacks the support of handover management for real-time streaming applications. In this paper, we propose a new fast handoff mechanism which eradicates the scanning delay. The proposed scheme uses the information of link quality (LQ) of the neighboring coordinators (COs), and on the basis of this information it selects an appropriate CO for handoff. The proposed scheme is evaluated through extensive simulations which show its strength and accuracy in the context of switching of high streaming data from one CO to another.